2020
DOI: 10.1177/0033354920966026
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV Preexposure Prophylaxis Initiation Among Public Health Clients in Rural and Small Urban Areas in Iowa

Abstract: Objective Preexposure prophylaxis (PrEP) is a safe and effective method for HIV prevention, but little is known about PrEP uptake in rural and small urban areas. We described rates and predictors of HIV PrEP initiation among public health clients in rural and small urban areas in Iowa. Methods This was a prospective cohort study of clients with PrEP indications served by HIV testing and disease intervention specialist/partner services (DIS/PS) programs in public health departments in Iowa from February 1, 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…17,63 Studies from Seattle, Chicago, and Iowa suggest that between one-quarter and one-third of HIV-negative men who have sex with men (MSM) who are not on PrEP can be successfully linked to PrEP through PS. [64][65][66] Data on the success of PS in relinking out-of-care HIV-positive persons to care are limited, but a study of syphilis and gonorrhoea PS in six US jurisdictions found that 29% of previously diagnosed HIV-positive persons receiving PS for syphilis or gonorrhoea in 2016-17 -17 574 peoplewere out of care or not virally suppressed, suggesting that PS could play a large role in increasing engagement in HIV care. 67 In general, the marginal cost of integrating these outcomes into the services provided to people who are already receiving PS is low.…”
Section: Integrating Outcomes Other Than Sti Treatment Into Partner N...mentioning
confidence: 99%
“…17,63 Studies from Seattle, Chicago, and Iowa suggest that between one-quarter and one-third of HIV-negative men who have sex with men (MSM) who are not on PrEP can be successfully linked to PrEP through PS. [64][65][66] Data on the success of PS in relinking out-of-care HIV-positive persons to care are limited, but a study of syphilis and gonorrhoea PS in six US jurisdictions found that 29% of previously diagnosed HIV-positive persons receiving PS for syphilis or gonorrhoea in 2016-17 -17 574 peoplewere out of care or not virally suppressed, suggesting that PS could play a large role in increasing engagement in HIV care. 67 In general, the marginal cost of integrating these outcomes into the services provided to people who are already receiving PS is low.…”
Section: Integrating Outcomes Other Than Sti Treatment Into Partner N...mentioning
confidence: 99%
“…Data from the US suggest that APS can be an effective platform for promoting preexposure prophylaxis (PrEP), but little data exists on this from contexts outside the United States. [12][13][14][15][16][17] Namibia is approaching the UNAIDS 95-95-95 targets with an estimated 92% of people living with HIV (PLHIV) diagnosed, 99% of diagnosed PLHIV on antiretroviral therapy (ART), and 94% of patients on ART virally suppressed. 18 Starting in October 2019, the Namibian MHSS, technically supported by the International Training and Education Center for Health (I-TECH) at the University of Washington, implemented facility-based APS in 22 MHSS clinical sites in a focused effort to increase HIV case finding.…”
mentioning
confidence: 99%
“…Finally, there are few data on the effectiveness of efforts to integrate outcomes other than HIV testing into APS programs. Data from the US suggest that APS can be an effective platform for promoting preexposure prophylaxis (PrEP), but little data exists on this from contexts outside the United States 12–17 …”
mentioning
confidence: 99%